THE IMPACT OF REGIONAL AUTONOMY POLICY FOR ECONOMIC GROWTH IN EAST JAVA - Wahyu Kurniana; Wahyu Kurniani; Irvan Sepfiandy; Evan Gyovani (Universitas Negeri Malang, 2017)
This study aims to determine the effect of local revenue, general allocation funds and special allocation funds to local spending and economic growth as well as to find out the possibility of Flypaper Effect on District/City shopping in East Java Province. The population in this study is all districts/cities located in East Java Province. Data analysis was performed by panel data regression using Eviews 8 and Microsoft Excel 2010 program. The results of this study indicate that local revenues, general allocation funds, and special allocation funds have a positive and significant impact on district/city expenditure in East Java. Local revenues, general allocation funds, and special allocation funds have a positive and significant impact on the economic growth of districts/cities in East Java Province. While variable of regional expenditure has negative and significant influence on economic growth of district/city in East Java Province. Local revenues, general allocation funds and special allocation funds indirectly through regional expenditures on district economic growth in East Java Province are negative and regional expenditures are not proven to be intermediate variables. Value of Coefficient of General Allocation Fund and Special Allocation Fund is bigger than the value of the original revenue coefficient so that it can be said that there has been Flypaper Effect on the expenditure of District/City in East Java Province in 2010-2014.Keywords: Economic Growth, Regional Autonomy, Flypaper EffectJEL Classification: R11, R58